2014
DOI: 10.1021/ef402150z
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties of Petrologic End-Members from Alberta Oil Sands and Their Relationship with Mineralogical and Chemical Composition

Abstract: Clays cause problems in all crucial stages of bitumen extraction, and they affect bitumen recovery and waste management. It is thus of great importance to understand the mineralogy, chemistry, and surface properties of clays to improve both bitumen recovery and tailings treatment. Four petrologically different types of Alberta oil sands orescalled "endmembers"were examined in this study by cation exchange capacity (CEC), specific surface area (SSA), total specific surface area (TSSA), and negative layer char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 82 publications
(140 reference statements)
0
14
0
Order By: Relevance
“…We demonstrate that more concentrated peroxide solutions are not capable of completely removing organic carbon even from nonswelling clay minerals (kaolinite, illite, and chlorite), which implies that refractive organics in clay rich materials are not protected from degradation exclusively by nanoconfinement within the clay mineral interlayers , and suggests formation of particularly stable bonds between clay mineral layers and organic radicals . In addition, our results confirm observations by Osacky et al and Geramian et al that the bitumen associated with clay minerals is particularly resistant to the solvent extraction resulting in a problematic recovery of bitumen from sands.…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrate that more concentrated peroxide solutions are not capable of completely removing organic carbon even from nonswelling clay minerals (kaolinite, illite, and chlorite), which implies that refractive organics in clay rich materials are not protected from degradation exclusively by nanoconfinement within the clay mineral interlayers , and suggests formation of particularly stable bonds between clay mineral layers and organic radicals . In addition, our results confirm observations by Osacky et al and Geramian et al that the bitumen associated with clay minerals is particularly resistant to the solvent extraction resulting in a problematic recovery of bitumen from sands.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 The results of these studies showed compositional differences among the petrologic end members and relationships between the mineral and chemical composition of the oil sands. 9,10 Furthermore, it has been revealed that the surface properties (cation exchange capacity, specific surface area, and layer charge density) of the petrologic end members are primarily controlled by mineralogy, mainly by the type and quantity of clay minerals. 10 The same studies have also demonstrated the difficulty in determining the effect of individual parameters (mineralogy, chemistry, and surface properties) of petrologic end members on nonaqueous solvent bitumen extraction.…”
Section: ■ Introductionmentioning
confidence: 94%
“…9,10 Furthermore, it has been revealed that the surface properties (cation exchange capacity, specific surface area, and layer charge density) of the petrologic end members are primarily controlled by mineralogy, mainly by the type and quantity of clay minerals. 10 The same studies have also demonstrated the difficulty in determining the effect of individual parameters (mineralogy, chemistry, and surface properties) of petrologic end members on nonaqueous solvent bitumen extraction. To overcome this problem, some authors 11−13 have used artificial oil sands systems where compositional variables can be controlled so that individual factors affecting bitumen recovery can be studied.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The composition of oil sand is one of the most important factors that affects the extraction process of bitumen from oil sand, because a small amount of suspended fine solids remains in the bitumen. Among the components that cause this problem, suspended fine solids, more specifically the clay minerals and the asphaltenes, deserve special attention (Wang et al 2013(Wang et al , 2014Osaky et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The asphaltene adsorption on the surface of clay minerals plays an important role in the oil industry: (i) altering the wettability, in which particles in contact with the crude oil change their hydrophobicity character; (ii) causing the fouling of the catalysts; and (iii) contaminating the bitumen, reducing the quality of the oil and hence generating higher costs (Dudášová et al 2008;Lucas et al 2009Lucas et al , 2015Nikakahtari et al 2013;Wang et al 2013;Osaky et al 2014;Maravilha and Spinelli, 2018;Neuhaus et al 2019). Although many researches have been done on tailing ponds treatment, this process still need to be improved (Nikakahtari et al 2013;Reis et al 2016;Vajihinejad et al 2017;Gumfekar and Soares 2018a, b;Vajihinejad and Soares 2018;Younes et al 2018).…”
Section: Introductionmentioning
confidence: 99%